The Efficacy of Statin on Coronary Artery Calcification based on Agatston Score: An Updated Meta-analysis of Randomized Control Trials - Sony Hilal Wicaksono; Yusra Pintaningrum; Ketut Angga Aditya Putra Pramana (Postgraduate, University of Mataram, 2025)
The purpose of this study is to assess the efficacy of statin treatment on coronary artery calcifcation (CAC) in patients with asymptomatic coronary artery disease (CAD). For randomized controlled trials (RCTs) that assess the efficacy of statin treatment on CAC in patients with asymptomatic CAD, we searched in PubMed, ScienceDirect, and Cochrane. The included publications were subjected to meta-analyses using Review Manager v5.4. In comparison to control, patients with statistically significant had a lower Agatston score (MD -46.25; 95% CI -56.37 - -36.12; p < 0.00001) and had lower CAC volume (MD -24.36; 95% CI -38.21 - -10.51; p = 0.0006). Statin treatment was also linked to a decreased risk of atherosclerotic cardiovascular disease (ASCVD) events (OR 0.60, 95% CI 0.43-0.83; p = 0.002). According to our meta-analysis, the statin treatment was significant to lowering the Agatston score and CAC volume in patients with aysmptomatic CAD. Statin was also linked to a decreased risk of ASCVD events compared to control